Assessment of Farmer Producer Organizations- An Indian Perspective - Nayaji, Anayatullah; Dixit, Sharad (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Indian economy was already in the grip of a prolonged slowdown before the coronavirus hits the country The total lockdown due to this Covid19 outbreak damages economic structure (rural and urban) of country. Indian agriculture severely faced problem due to this lockdown by hampering on supply chain, production, harvesting etc. Agriculture and its allied sectors is the largest livelihood provider in India, more so in the vast rural areas. Farmers from small and marginal land holding face various challenges in having access to inputs and marketing facilities. In the last several years Government of India has encouraged farmer producer organizations (FPOs) to help small and medium farmers. There are number of study have been conducted on impact of FPOs on farmers income and their standard of living. This paper tried to capture insights of FPOs and its challenges. Paper also suggested some measures to improve the condition of FPOs.